A Folha em cinco minutos: estratégias da narrativa jornalística na temporalidade do instantea - Yasmine Hofmann Rodrigues (2010)
In undertaking a study of narrative and its temporality in Folha Corrida Notícias em Cinco Minutos we believe to be new discoveries about the products In the printed media, because there seem to exist in both elements of the narrative classic of journalism, as of the new trend languages that media visible to our eyes. The intention throughout this work will be understood as processes that temporality of narrative journalism in this section to demonstrate that the print journalism has adopted new perspectives of the market and communication to interact with their readers. We want to decode the marks of those news stories that are presented to the recovery of the daily spot in layout pages with light, color and with almost telegraphic text that can be read on the journey from home to work. The importance of this study is precisely in decoding this set of narratives that has been setting in a new product for its contemporary printed graphics and text, as a kind of Jornalism of Almanac.